Taurine 8 : Volume 2: nutrition and metabolism, protective role, and role in reproduction, development, and differentiation - L'Amoreaux, William J.; El Idrissi, Abdeslem (Advances in Experimental Medicine and Biology, 2013)
Taurine 8 represents the combined efforts of investigators on the roles of the amino acid taurine on human health and disease. The chapters covered in this book are directly derived from presentations of the contributors at the 18th International Taurine Meeting held in Marrakech, Morocco in April 2012. The purpose of this book is to disseminate current findings on taurine's contribution in several organ systems. This book covers the following topics: Taurine in Nutrition and Metabolism, the Protective Role of Taurine, and the Role of Taurine in Reproduction, Development, and Differentiation. Dr. Abdeslem El Idrissi, College of Staten Island and Dr. William L'Amoreaux, College of Staten Island,  were co-chairs of the Organizing Committee for the meeting.   Data presented at this meeting provided compelling evidence that taurine is not only cytoprotective in cardiomyocytes, but also is a potent GABA agonist, whereby it can facilitate vasodilation of conducting arteries. Taurine conjugates, such as taurine chloramine, may protect cells from oxidative stress via increased HO-1 expression. In adult rodents, taurine has a potent effect on plasma glucose levels, likely through the release of insulin in pancreatic beta cells. As a potential neurotransmitter, taurine is known to work via the GABAergic system, but current research presented at this meeting suggest that taurine may interact with glutamate and serotonin receptors as well. Data are also presented to demonstrate the protective roles of taurine on neurons in neuroblastoma. Perhaps the most important and exciting presentation is the role of taurine and alcohol: the combination may be lethal. Data are also presented at this meeting of the potential role taurine may have as an adjuvant treatment with cisplatin in chemotherapy.